Lipids in Plant and Algae Development - Nakamura, Yuki; Li-Beisson, Yonghua (Subcellular Biochemistry, 2016)
This book summarizes recent advances in understanding the functions of plant and algal lipids in photosynthesis, in development and signaling, and in industrial applications. As readers will discover, biochemistry, enzymology and analytical chemistry, as well as gene knock-out studies have all contributed to our rapidly increasing understanding of the functions of lipids. In the past few decades, distinct physical and biochemical properties of specific lipid classes were revealed in plant and algal lipids and the functional aspects of lipids in modulating critical biological processes have been uncovered. These chapters from international authors across relevant research fields highlight the underlying evolutionary context of lipid function in photosynthetic unicellular and multicellular organisms. The book goes on to encompass what lipids can do for industrial applications at a time of fascination with plants and algae in carbon fixation and as sources for production of food, energy and novel chemicals. The developmental context is a part of the fresh and engaging perspective that is presented in this work which graduate students and scientists will find both illuminating and useful.